Efficacy and safety of febuxostat in the treatment of hyperuricemia in stable kidney transplant recipients - Sofue T; Inui M; Hara T; Nishijima Y; Moriwaki K; Hayashida Y; Ueda N; Nishiyama A; Kakehi Y; Kohno M (Drug Design, Development and Therapy, 2014)
Tadashi Sofue,1 Masashi Inui,2 Taiga Hara,1 Yoko Nishijima,1 Kumiko Moriwaki,1 Yushi Hayashida,3 Nobufumi Ueda,3 Akira Nishiyama,4 Yoshiyuki Kakehi,3 Masakazu Kohno1 1Division of Nephrology and Dialysis, Department of Cardiorenal and Cerebrovascular Medicine, Kagawa University, Kagawa, 2Department of Urology, Tokyo Women's Medical University, Tokyo, 3Department of Urology, 4Department of Pharmacology, Kagawa University, Kagawa, Japan Background: Post-transplant hyperuricemia (PTHU), defined as serum uric acid concentration ≥7.0 mg/dL or need for treatment with allopurinol or benzbromarone, reduces long-term allograft survival in kidney transplant recipients. Febuxostat, a new nonpurine selective xanthine oxidase inhibitor, is well tolerated in patients with moderate renal impairment. However, its efficacy and safety in kidney recipients with PTHU is unclear. We therefore assessed the efficacy and safety of febuxostat in stable kidney transplant recipients with PTHU. Methods: Of 93 stable adult kidney transplant recipients, 51 were diagnosed with PTHU (PTHU group) and 42 were not (NPTHU group). Of the 51 patients with PTHU, 26 were treated with febuxostat (FX group) and 25 were not (NFX group), at the discretion of each attending physician. One-year changes in serum uric acid concentrations, rates of achievement of target uric acid (<6.0 mg/dL), estimated glomerular filtration rates in allografts, and adverse events were retrospectively analyzed in the FX, NFX, and NPTHU groups. Results: The FX group showed significantly greater decreases in serum uric acid (-2.0±1.1 mg/dL versus 0.0±0.8 mg/dL per year, P<0.01) and tended to show a higher rate of achieving target uric acid levels (50% versus 24%; odds ratio 3.17 [95% confidence interval 0.96–10.5], P=0.08) than the NFX group. Although baseline allograft estimated glomerular filtration rates tended to be lower in the FX group than in the NFX group (40±14 mL/min/1.73 m2 versus 47±19 mL/min/1.73 m2), changes in allograft estimated glomerular filtration rate were similar (+1.0±4.9 mL/min/1.73 m2 versus -0.2±6.9 mL/min/1.73 m2 per year, P=0.50). None of the patients in the FX group experienced any severe adverse effects, such as pancytopenia or attacks of gout, throughout the entire study period. Nephrologists were more likely than urologists to start febuxostat in kidney transplant recipients with PTHU (69% versus 8%). Conclusion: Treatment with febuxostat sufficiently lowered uric acid levels without severe adverse effects in stable kidney transplant recipients with PTHU. Keywords: post-transplant hyperuricemia, febuxostat, uric acid, chronic kidney disease